Embedded software developments in KM3NeT phase I. (9th December 2021) - van Beveren, V.; Real, D.; Chiarusi, T.; Calvo, D.; Mastroianni, S.; Musico, P.; Pellegrini, G.; Jansweijer, P.; Colonges, S.; Bozza, C.; Filippini, F.; Nicolau, C.; et al.
Abstract: The KM3NeT collaboration has already produced more than one thousand acquisition boards, used for building two deep-sea neutrino detectors at the bottom of the Mediterranean Sea, with the aim of instrumenting a volume of several cubic kilometers with light sensors to detect the Cherenkov radiation produced in neutrino interactions. The so-called digital optical modules, house the PMTs and the acquisition and control electronics of the module, the central logic board, which includes a Xilinx FPGA and embedded soft processor. The present work presents the architecture and functionalities of the software embedded in the soft processor of the central logic board.